Medicinal Plant Images - Edwin Cock, Ian (Pharmacognosy Communications)
Terminalia ferdinandiana (commonly known as Kakadu plum, gubinge, billy goat plum and salty plum) is an endemic Australian tree which occurs in tropical grassland regions of northern Australia. The fruit has traditional uses for indigenous Australians as food and as a medicinal plant.1,2 Recent studies have reported Kakadu plum to be extremely high in antioxidants and to be the richest naturally occurring source of vitamin C.3,4 As high antioxidant levels have previously been demonstrated to act as preventative effects against the development of degenerative chronic diseases such as cancer, cardiovascular diseases, neural degeneration, diabetes and obesity, it has been postulated that Kakadu plum fruit may also be an effective preventative against these diseases.2 Recent studies have shown Kakadu plum fruit extracts to be effective at inhibiting the growth of a panel of microbes.5 The photograph depicts immature fruit and was taken in Darwin, Australia by Dr Ian Cock in January 2014.